Diels-Alder based, thermo-reversible cross-linked epoxies for use in self-healing composites. (19th November 2015) - Turkenburg, D.H.; Fischer, H.R.
Abstract: Epoxy resins are functionalized with Diels-Alder based thermo-reversible crosslinks to enable the fabrication of composites that are capable of multiple self-healing-repair processes. The key challenge in realizing a structural combination of conventional epoxy amine systems with furfuryl and maleimide functional groups is to achieve a high conversion in the reversible cross-linked polymer network formation while avoiding the major side-reactions. We have developed a two-step process consisting of a bulk prepolymerization reaction followed by a network formation step. The second step is performed in an extruder to realize a good mixing at high temperatures, while keeping the residence time at that temperature short to avoid maleimide side-reactions. The obtained oligomers are characterized using NIR, NMR, DSC, GPC analyses while solvent exposure tests and rheological measurements are performed to prove the formation of a thermo-reversible network and study their behavior in relation to the cross-linker concentration. Densely cross-linked, solvent resistant polymeric networks are obtained that maintain the ability to un-crosslink and thus regaining fluid behavior at elevated temperatures for at least five subsequent heat cycles. Glass fiber reinforced polymer composite films, which are fabricated using these resins, demonstrate that the thermo-reversible effect is strong enough to achieve full self-healing of a severely cracked and delaminated test specimen. Graphical abstract: Highlights: An epoxy amine system is combined with a Diels-Alder (furfuryl maleimide) system. The highly crosslinked thermo-reversible polymer network flows at high temperature. Self-healing of a composite of glass fibers infused with the resin is demonstrated.